2009
DOI: 10.1007/bf03214953
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the reactant concentration in selective hydrogenation of 1,3-butadiene over supported gold catalysts under alkene rich conditions: A consideration of reaction mechanism

Abstract: This article is about the reaction of selective hydrogenation of 1,3-butadiene performed in an excess of alkenes (propene/butadiene ratio = 100) over supported gold catalysts, so as to mimic the conditions of purification of light alkenes (C4 cuts) from the presence of impurities (highly unsaturated compounds, 1-3%). Gold was found highly selective (close to 100%, no propane or butane formation) for the hydrogenation of butadiene to butenes at 100% conversion of butadiene. The influence of the concentrations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
47
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(57 citation statements)
references
References 25 publications
10
47
0
Order By: Relevance
“…o and Au/CNTs-m catalysts. It should be pointed out that the outstanding feature of high selectivity for butenes was earlier observed for hydrogenation of BD over oxide-supported gold catalysts [26,39,43,45,53]. The reason for the high selectivity could be due to the weak activation/dissociation of molecular H 2 and adsorption of monobutenes on gold catalyst.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…o and Au/CNTs-m catalysts. It should be pointed out that the outstanding feature of high selectivity for butenes was earlier observed for hydrogenation of BD over oxide-supported gold catalysts [26,39,43,45,53]. The reason for the high selectivity could be due to the weak activation/dissociation of molecular H 2 and adsorption of monobutenes on gold catalyst.…”
Section: Discussionmentioning
confidence: 94%
“…In the case of gold catalysts, Buchanan and Webb [52] deduced on the basis of the result of first order in hydrogen and zero order in BD that step 1 of dissociative adsorption of H 2 was the rate-determining step over Au/Al 2 O 3 catalyst for hydrogenation of BD. Hugon et al [53] reported recently that the reaction order was 0.7 with respect to H 2 and 0.2 with respect to BD over Au/Al 2 O 3 catalyst for the selective hydrogenation of BD in propene-rich atmosphere. Although no kinetic data including reaction order and apparent activation energy were addressed, H 2 dissociation was presumed to be the rate-determining step over oxidesupported gold catalysts on the basis of the reaction results of hydrogenation of BD and crotonaldehyde [43,54].…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Completely selective hydrogenation of ethyne and other alkynes on Au catalysts has frequently been observed, rates being faster than for those of alkenes [20][21][22], unlike the situation with metals of groups 8 to 10 [19]; detailed kinetic and mechanistic studies are however quite rare [22]. In particular, it is not clear whether high selectivity arises from surfaces partly covered with 'carbonaceous residues', as is thought to be the case with Pd catalysts [23], but probably not, as high selectivity is shown from the start [22].…”
Section: Hydrogenation Of Alkynesmentioning
confidence: 99%
“…To this effect, Hugon and co-workers (47,65) investigated the selective hydrogenation of 1,3-butadiene in propene by gold supported on zirconia, ceria, alumina and titania. In contrast to the results of Zhang et al (63,64) the Au 3+ species was inactive and only became active once reduced to Au 0 under the reactant stream.…”
Section: And C 5 Hydrocarbonsmentioning
confidence: 99%